If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x2+6x-91=0*
We move all terms to the left:
x2+6x-91-(0*)=0
We add all the numbers together, and all the variables
x2+6x-91-0=0
We add all the numbers together, and all the variables
x^2+6x-91=0
a = 1; b = 6; c = -91;
Δ = b2-4ac
Δ = 62-4·1·(-91)
Δ = 400
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:x_{1}=\frac{-b-\sqrt{\Delta}}{2a}x_{2}=\frac{-b+\sqrt{\Delta}}{2a}\sqrt{\Delta}=\sqrt{400}=20x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(6)-20}{2*1}=\frac{-26}{2} =-13x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(6)+20}{2*1}=\frac{14}{2} =7
| 11c=78=5c=48 | | 2(5a+4)=48 | | -21=7(7x-24) | | -2(5x+7)=-4 | | -6(4+x)=18 | | m-56=-5 | | 4(2m-7)=3(2m/4) | | 4x-1+6x-4=7 | | 12x^2-68x=-40 | | 12x^2-40x+32=0 | | x−8+8=12 | | (y+18)^2=77 | | 6x-12x=3x+30 | | -(x-1)=-2-4x | | 28-3b=-4(5b-7) | | 2(4x-7)=31-x | | 9(3x-5)=9* | | x–37/9=7 | | x–379=7 | | 3x+3/7x=5x-11/8x-7 | | -10+2x=2x | | 5/6x+4/6=-9 | | 5*(2x)-10=30 | | 6(g-5)=10g+22 | | 1/2x+2/4=8 | | 7c-3=3c+25 | | 7(g-5)=10g+22 | | 93x=5 | | (x+1)/(x-+)=1 | | 10b+8=4b+38 | | 2(3b–1)=40 | | x-10=2/3(180-x) |